2012
DOI: 10.1016/j.smallrumres.2011.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of Sicilian sheep breeds using microsatellite markers

Abstract: a b s t r a c tGenetic diversity studies in domestic animals aim at evaluating genetic variation within and across breeds mainly for conservation purposes. In Sicily, dairy sheep production represents an important resource for hilly and mountain areas economy. Their milk is used for the production of traditional raw milk cheeses, sometimes protected designation of origin (PDO) cheeses. In some cases, the quality of these products is linked to a specific breed, i.e. mono-breed labelled cheeses and it is therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
39
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 28 publications
14
39
1
2
Order By: Relevance
“…The population parameters observed in the present study were also higher than those observed in other sheep breeds, both locally adapted, and exotic, from Spain (Calvo et al, 2011), India (Arora et al, 2011), Italy (Lasagna et al, 2011), and Cuba (Álvarez et al, 2012). Tolone et al (2012) found very similar results when analyzing five Sicilian sheep breeds with 20 microsatellites (average of 10.95 alleles per locus for the native sheep Pinzirita). Baumung et al (2006) reported an average of 15 alleles, when 25 microsatellite markers were genotyped in 11 Austrian breeds.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The population parameters observed in the present study were also higher than those observed in other sheep breeds, both locally adapted, and exotic, from Spain (Calvo et al, 2011), India (Arora et al, 2011), Italy (Lasagna et al, 2011), and Cuba (Álvarez et al, 2012). Tolone et al (2012) found very similar results when analyzing five Sicilian sheep breeds with 20 microsatellites (average of 10.95 alleles per locus for the native sheep Pinzirita). Baumung et al (2006) reported an average of 15 alleles, when 25 microsatellite markers were genotyped in 11 Austrian breeds.…”
Section: Discussionmentioning
confidence: 53%
“…This result may be due to the small sample population (15 individuals), and due to the population being consolidated with planned genetic crosses established from breeding programs. Several studies using locally adapted or native breeds confirmed that these breeds have more number of loci in HWE when compared to more specialized breeds (McManus et al, 2010;Paiva et al, 2011a;Tolone et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Within Sicilian flocks, rams and ewes are reared together; therefore mating with close relatives could be quite frequent. Moreover, the reduced or absent exchange of rams between different flocks may have induced the development of a substructure within this population (Tolone et al, 2012). This could be more frequent where the assessment of parentage is not carried out (Pariset et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Within the most visited farms in the investigation, inbreeding resulted from the lack of control in mating between animals which led to a lot of mating between related individuals, thus, eventually leading to the heterozygous reduction in the populations (MartĂ­nez et al, 2010 On the other hand most of production systems in the country have one or two sires to mate with all the females of the herd, which could reduce significantly the genetic diversity in the populations and contribute to the reduction of heterozygous individuals in the population (Tolone et al, 2012).…”
Section: Genetic Diversity Between Breedsmentioning
confidence: 99%